Dioscin Improves Pyroptosis in LPS-Induced Mice Mastitis by Activating AMPK/Nrf2 and Inhibiting the NF-κB Signaling Pathway. (31st December 2020) - Ran, Xin; Yan, Zhang; Yang, Yuanxi; Hu, Guiqiu; Liu, Juxiong; Hou, Shuang; Guo, Wenjin; Kan, Xingchi; Fu, Shoupeng
Abstract : Dioscin, a natural steroid saponin, has been shown to have anti-inflammatory effects, but its protective mechanism against mastitis is still unknown. NLRP3 inflammasome and pyroptosis play important roles in the pathogenesis of many inflammatory diseases, including mastitis. The purpose of this study was to explore the effect of dioscin on lipopolysaccharide- (LPS-) induced mastitis in vivo and in vitro and its mechanism of action. In vivo experiments, dioscin can reduce the inflammatory lesions and neutrophil motility in mammary tissue. Moreover, dioscin also can reduce the production of proinflammatory factors such as interleukin-1 beta (IL-1 β ) and inhibit the activation of NLRP3 inflammasome in LPS-induced mice mastitis. In vitro experiments, the results showed that dioscin inhibited the inflammatory response and the activation of NLRP3 inflammasome, but the survival rate of mouse mammary epithelial cells (mMECs) induced by LPS+ATP is increased. Subsequently, the experiment convinces that dioscin can reduce LPS+ATP-induced mMEC pyroptosis by adding Ac-DEVD-CHO (a caspase-3 inhibitor). Further mechanistic studies demonstrate that dioscin can activate AMPK/Nrf2 to inhibit NLRP3/GSDMD-induced mMEC pyroptosis. In summary, this paper reveals a novel function of dioscin on mMEC pyroptosis and provides a new potential therapy of dioscin for the treatment and prevention of mastitis.